La majorité oubliée: le rôle des femmes à Montréal au 19e siècle - Cross, D. Suzanne (Les femmes dans la société québécoise, 1977)
Keywords: Femmes

Historiennes engagées et femmes patriotes: la révolution de 1837-1838 et la place des femmes dans l'histoire du Québec - Arsenault, Mathieu (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Femmes; Histoire; Rébellions

Des femmes anglo-protestantes s'attaquent aux questions sanitaires. Les multiples facettes des soins de santé à Montréal, au XIXe siècle et au début du XXe siècle - Harvey, Janice (L'incontournable caste des femmes. Histoires des services de santé au Québec et au Canada, 2012)
Keywords: Anglophones; Bénévolat; Femmes; Montreal Local Council of Women; Protestants

L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

Les femmes patriotes: de la réalité à la fiction - Aubin, Georges (Bulletin d'histoire politique, 2003)
issued: 2003-23-00
Keywords: Femmes; Rébellions

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

1810-1895: l’entrée des femmes dans l’arène sportive - Janson, Gilles (Cap-aux-Diamants, 2013)
issued: 2013-21-00
Keywords: Femmes; Patin

Les femmes et le vote au Bas-Canada de 1792 à 1849 - Picard, Nathalie (Université de Montréal, 1992)
Keywords: Femmes; Élections

Rhétorique et autoreprésentation: la pratique épistolaire des femmes en temps d'insurrections - Bédard, Mylène (Université de Laval, 2014)
Keywords: Femmes; Écrivains

Écrire en temps d'insurrections: pratiques épistolaires et usages de la presse chez les femmes patriotes (1830-1840) - Bédard, Mylène (Presses de l'Université de Montréal, 2016)
Keywords: Femmes; Écrivains

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Le travail des femmes célibataires de l'élite et la famille pendant la période préindustrielle à Montréal - Fortin, Jonathan (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Reporter: L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles
Keywords: Famille; Femmes; Fourrure; Marchands; Travail

Rire après les Rébellions: les femmes comme miroir déformant de l’actualité canadienne dans Le Fantasque de Napoléon Aubin - Bédard, Mylène (Mens, 2018)
issued: 2018-23-00/2019-21-00
Keywords: Aubin; Napoléon; Femmes; Humour; Journalistes; Rébellions

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre; Joseph; Femmes; Guibord; Joseph; Institut canadien; Mariage; Renaud; Marie-Zoé-Aimée; Trudel; François-Xavier-Anselme; Ultramontains

Mère Gamelin, femme de compassion (s.é., 1984)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

La femme au coeur attentif: mère Gamelin - Nadeau, Eugène (Providence Montréal, 1969)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

Par le chemin du roi une femme est venue - Duval, Germaine (Bellarmin, 1982)
Keywords: Communautés religieuses; Durocher; Eulalie; Soeurs des Saints Noms de Jésus et de Marie

Madame James McGill (1747-1818): Marie-Charlotte Guillimin, ou, La vie d'une femme mondaine à Montréal au dix-huitième siècle - Tanguay, Lynda (Université McGill, 1993)
Keywords: Bourgeoisie; McGill; James

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

"Due Attention Has Been Paid to All Rules": Women, Tavern Licences, and Social Regulation in Montreal, 1840–1860 - Poutanen, Mary Anne (Histoire sociale / Social History, 2017)
Number: 101
Keywords: Femmes

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Quebec Women: a History - Collectif Clio (Women's Press, 1987)
Translators: _:n14097
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Canadian City. Essays in Urban History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in Nineteen Century Montreal - Cross, D. Suzanne (The Social Development of Canada - Readings, 1983)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Neglected Majority: Essays in Canadian Women's History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (Histoire sociale / Social History, 1973)
Number: 12
Keywords: Femmes

"A Most Detestable Crime": Gender Identities and Sexual Violence in the District of Montreal, 1803-1843 - Ramos, Sandy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Number: 1
Keywords: Femmes

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Veuves et électrices : genre, citoyenneté et élection partielle à Montréal en 1832 - Bradbury, Bettina (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Élections

The Geography of Prostitution in an Early Nineteenth-Century Urban Centre: Montreal, 1810-1842 - Poutanen, Mary Anne (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Prostitution

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Femmes; Mariage

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

Les maîtresses d'écoles indépendantes: une contribution essentielle à l'éducation de la jeunesse montréalaise du premier tiers du XIXe siècle - Dufour, Andrée (Les bâtisseuses de la Cité, 1993)
Keywords: Enseignants; Femmes

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
issued: 2009-23-00
Keywords: Bourgeoisie; Femmes

Widows Negotiate the Law: The First Year of Widowhood in Early-Nineteenth-Century Montreal - Bradbury, Bettina (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Veuvage

Wife to Widow: Lives, Laws, and Politics in Nineteenth-Century Montreal - Bradbury, Bettina (University of British Columbia Press, 2011)
Keywords: Femmes; Veuvage

Bonds of Friendship, Kinship, and Community: Gender, Homelessness, and Mutual Aid in Early-Nineteenth-Century Montreal - Poutanen, Mary Anne (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Itinérance

Widows at the Hustings: Gender, Citizenship, and the Montreal By-Election of 1832 - Bradbury, Bettina (Women on their Own. Interdisciplinary Perspectives on Being Single, 2008)
Keywords: Femmes; Élections

Teachers, Gender, and Bureaucratizing School Systems in Nineteenth Century Montreal and Toronto - Danylewycz, Marta; Prentice, Alison Leeds (History of Education Quarterly, 1984)
issued: 1984-21-00
Keywords: Enseignants; Femmes

The Legal Rights of Masters, Mistresses and Domestic Servants in Montreal, 1816-1829 - Hogg, Grace Laing (Université McGill, 1989)
Keywords: Domestiques; Femmes

Les domestiques en milieu urbain au début du XIXe siècle - Lacelle, Claudette (Parcs Canada, 1980)
Keywords: Domestiques; Femmes

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Women at the Hustings: Gender, Citizenship, and the Montreal By-Elections of 1832 - Bradbury, Bettina (Rethinking Canada: the Promise of Women’s History, 2011)
Keywords: Femmes; Élections

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

"Elles ne se marièrent pas et eurent beaucoup d'enfants": analyse du discours institutionnel traitant de la mère célibataire au Québec au milieu du XXe siècle - Turcotte, Géraud (Université Laval, 1990)
Keywords: Famille; Femmes

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
issued: 2010-24-00
Keywords: Confection; Femmes

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
issued: 1984-23-00
Keywords: Famille; Femmes

«Toujours je sens mon âme se balancer entre les joies et les peines»: le paysage émotionnel de Marie-Louise Globensky (1849-1919) observé à travers ses écrits personnels - Doucet, Sophie (Université du Québec à Montréal, 2019)
Keywords: Bourgeoisie; Femmes

Beyond Brutal Passions. Prostitution in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (McGill-Queen's University Press, 2015)
Keywords: Femmes; Prostitution

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Charivari, libéralisme et genre au Bas-Canada, 1820-1860 - Cournoyer, Amy (Université du Québec à Trois-Rivières, 2020)
Keywords: Femmes; Libéralisme

Les vocations féminines de la région montréalaise au XIXe siècle - Payette, Céline (Université du Québec à Montréal, 1991)
Keywords: Communautés religieuses; Femmes

« La force, la grâce, la souplesse »: l’éducation physique des jeunes filles canadiennes-françaises à Montréal (1860-1920) - St-Georges, Valérie (Université de Montréal, 2019)
Keywords: Femmes; Éducation physique

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
issued: 2022-21-00/2022-23-00
Keywords: Archives; Femmes; Écrivains

Debating Dower: Patriarchy, Capitalism and Widows' Rights in Lower Canada» - Bradbury, Bettina (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Mariage; Veuvage

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Number: 3
Keywords: Famille; Femmes; Veuvage

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

The Evolution of the Sexual Division of Labour in Teaching: A Nineteenth-Century Ontario and Quebec Case Study - Danylewycz, Marta (Histoire sociale / Social History, 1983)
Number: 31
Keywords: Enseignants; Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Number: 33
Keywords: Famille; Femmes; Travail

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Absorbing Junior: the Use of Patent Medicines as abortifacients in Nineteenth Century Montreal - Gossage, Peter (The Register, 1982)
Number: 1
Keywords: Avortement; Femmes; Médecine

Shelter from the Hurry? Hospitality in Montreal, 1836-1913 - Poutanen, Mary Anne; Olson, Sherry (Architectures of Hurry - Mobilities and Modernity in Urban Environments, 2018)
Reporter: Architectures of Hurry - Mobilities and Modernity in Urban Environments
Keywords: Auberges; Femmes; Hôtellerie

Women in Westmount (The Westmount Historian, 2020)
Number: 2
Keywords: Femmes; Peinture; Élections

Histoire d’un système judiciaire à plusieurs vitesses: analyse intersectionnelle des procès pour meurtre dans la juridiction de Montréal entre 1700 et 1760 - Berthelet, Marie-Ève (Université de Montréal, 2019)
Keywords: Autochtones; Criminalité; Femmes

"Every Attention Will Be Paid to the Satisfaction of the Guests": Angélique Archambault and Donegana’s Hotel, 1852-1864 - Poutanen, Mary Anne (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Femmes; Hôtellerie; Mariage

Robertine Barry, On l’appelait Monsieur - Desjardins, Sergine (Histoire Québec, 2024)
Keywords: Femmes; Journalistes; Patrie (La)

Domaine des soeurs grises de Montréal - Gauthier, Raymonde (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Femmes; Patrimoine; Soeurs Grises

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Intimacies in the Neighbourhood: Revisiting Sex Commerce, Families, and Criminal Court Records in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Family and Justice in the Archives. Historical Perspectives on Intimacy and the Law, 2024)
Keywords: Criminalité; Famille; Femmes; Prostitution

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson; William; Femmes; Université McGill

Le célibat féminin à Québec et Montréal au XVIIIe siècle: travail, famille et sociabilité - Fortin, Jonathan (Université de Sherbrooke, 2016)
Keywords: Famille; Femmes; Marchands; Travail

Public Houses and Hidden Networks: Roles of Women in Mid-Nineteenth-Century Montreal - Poutanen, Mary Anne; Olson, Sherry (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Auberges; Famille; Femmes; Hôtellerie

Le réseau de régulation sociale montréalais - Fecteau, Jean-Marie; Harvey, Janice (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

History of the Montreal Ladies' Benevolent Society 1815-1920 (s.é., 1920)
Keywords: Femmes; Montreal Ladies' Benevolent Society; Philanthropie

The Women's College, with Special Reference to Royal Victoria College, McGill University - Dudkiewicz, Zina (Université McGill, 1982)
Keywords: Femmes; Royal Victoria College; Université McGill

De la couventine à la débutante: signature féminine et mise en scène de soi dans la presse au XIXe siècle - Roy, Julie; Savoie, Chantal (Médias 19, 2012)
Keywords: Communautés religieuses; Couvents; Femmes; Journalistes

Montreal's Network of Social Regulation - Fecteau, Jean-Marie; Harvey, Janice (Montreal: The History of A North American City, 2018)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n62 Translators: _:n62435
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Le Bon-Pasteur et ses oeuvres à Montréal - Gouin, Édouard (Imprimerie de l'Institution des sourds-muets, 1916)
Keywords: Communautés religieuses; Femmes; Soeurs du Bon-Pasteur

Le financement des pensionnats de jeunes filles au Québec; le modèle de la Congrégation des Soeurs de Sainte-Anne, 1850-1950 - Champagne, Lucie (Université de Sherbrooke, 1989)
Keywords: Communautés religieuses; Femmes; Soeurs de Sainte-Anne

À chacune son rang. Les ''filles données'' des Soeurs Grises 1855-1905 - Gervais, Diane (Revue d'histoire de l'Amérique française, 2014)
issued: 2014-22-00/2014-23-00
Keywords: Communautés religieuses; Domestiques; Femmes; Soeurs Grises

Le financement des pensionnats de jeunes filles au Québec: le modèle de la Congrégation des Soeurs de Sainte-Anne, 1850-1950 - Dumont, Micheline; Champagne, Lucie (La Société canadienne d'histoire de l'Église catholique, sessions d'étude, 1986)
Keywords: Communautés religieuses; Femmes; Soeurs de Sainte-Anne

La tutelle des enfants mineurs au Bas-Canada: autorité domestique, traditions juridiques et masculinités - Garneau, Jean-Philippe (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-23-00
Keywords: Enfants; Famille; Femmes; Mariage; Veuvage

Les seigneuresses de l'île - Barthe, Marcel (Les Argoulets, 2024)
Keywords: Congrégation de Notre-Dame; Femmes; Île-des-Soeurs

Their benevolant design: conervative women and protestant child charities in Montreal - Harvey, Janice (McGill-Queen's University Press, 2024)
Keywords: Enfants; Femmes; Montreal Ladies' Benevolent Society; Protestants

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Une histoire sociale du curling au Québec, de 1807 à 1980 - Richard, Pierre (Université du Québec à Trois-Rivières, 2006)
Keywords: Clubs; Curling; Femmes; Francophones; Montreal Curling Club

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Taking the Veil in Montreal, 1840-1920: An Alternative to Marriage, Motherhood and Spinsterhood - Danylewycz, Marta (Université de Toronto, 1981)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Profession: Religieuse. Un choix pour les Québécoises (1840-1920) - Danylewycz, Marta (Boréal, 1988)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Taking the Veil: An Alternative to Marriage, Motherhood, and Spinsterhood in Quebec, 1840-1920 - Danylewycz, Marta (McClelland and Stewart, 1987)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Le Club des archères de Montréal existait-il réellement? - Martin, Gabriel (Histoire Québec, 2020)
Number: 1-2
Keywords: Clubs; Femmes; Histoire; Montreal Ladies Archery Club / Montreal Archery Club

On ne naît pas mère, on le devient : le parcours de Julie Papineau - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Famille; Femmes; Mariage; Papineau (famille); Papineau; Louis-Joseph; Rébellions

Journaux de jeunes filles: vers un moi autonome - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Dessaulles; Henriette (Fadette); Famille; Femmes; Le Normand; Michelle; Mariage; Écrivains

De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime - Smart, Patricia (Les Éditions du Boréal, 2014)
Keywords: Dessaulles; Henriette (Fadette); Famille; Femmes; Le Normand; Michelle; Marchand-Dandurand; Joséphine; Mariage; Papineau (famille); Rocbert de La Morandière; Élizabeth (Bégon; Élizabeth)